Psychological resilience and post-traumatic stress disorder as serial mediators between social connectedness and quality of life among individuals exposed to 2023 Kahramanmaras earthquakes - Karadag, Tugay; Parim, Coskun; Ozkan, Egemen; Ozkan, Batuhan; Tekeli, Fatma Noyan; Simsek, Gulhayat Golbasi; Satici, Seydi Ahmet (SPRINGER, 2025)
This research investigates the effects of social connectedness, psychological resilience, and post-traumatic stress disorder on the quality of life among those affected by the 2023 Kahramanmaras earthquakes in T & uuml;rkiye. Surveys were conducted with 207 university students directly or indirectly impacted by the disaster. The relationships between these factors were analyzed using structural equation modeling. The findings indicated that social connectedness had a significant direct effect on psychological resilience, post-traumatic stress disorder, and quality of life. Additionally, psychological resilience negatively influenced post-traumatic stress disorder, while post-traumatic stress disorder had a significant negative effect on quality of life. The analysis also uncovered indirect effects, demonstrating that psychological resilience and post-traumatic stress disorder mediated the link between social connectedness and quality of life. The findings have important implications for disaster recovery efforts, suggesting that interventions should focus on fostering individuals' sense of belonging by building meaningful relationships for better recovery outcomes.
Keywords: Earthquake; Post-traumatic stress disorder; Resilience; Social connectedness; Quality of life; PSYCHOMETRIC PROPERTIES; WENCHUAN EARTHQUAKE; SCALE; DEPRESSION; SURVIVORS; DISASTER; SUPPORT; VERSION; Geology; Meteorology & Atmospheric Sciences; Water Resources